Formation of Complex α-Imino Esters via Multihetero-Cope Rearrangement of α-Keto Ester Derived Nitrones - Bartlett, Samuel L.; Keiter, Kimberly M.; Zavesky, Blane P.; Johnson, Jeffrey S. (Synthesis, 2019)
A sequential benzoylation and multihetero-Cope rearrangement of α-keto ester derived nitrones has been developed. The reaction furnishes a diverse array of complex α-imino ester derivatives. The products can be transformed into amino alcohols via LiAlH4 reduction.
Keywords: rearrangement; ketones; imines; oxygenations; esters